Global Alliance Against Tobacco Marketing: Do Increased Taxation of Tobacco Products Decrease Tobacco Consumption? - Mukherjee, Amit; Ekanayake, E.M. (Journal of Applied Business and Economics, 2018)
The prevailing wisdom in tobacco control literature is that adroit use of taxation policy will reduce the prevalence of tobacco use because when tobacco prices go up, consumption goes down. Empirical evidence of this axiomatic inverse relationship has been sparse. This paper analyzes the effects of increased taxation on consumption of tobacco products in 136 countries during 2009-2015. Results indicate that there is weak negative relationship between change in adult smoking prevalence and change in taxation suggesting that higher tax rates on tobacco products tend to lower adult smoking prevalence, but in a modest rather than robust sort of way.